Design of floating photovoltaic structures using multiscale modelling approach - To, Gavan Lap Fung (Nanyang Technological University, 2022)
Global warming and the increasing emissions of greenhouse gases have for decades now, taken a toll on Earth’s environment. With the continual development of countries, the problem looks set to remain for the foreseeable future as energy demand continues to rise. In a bid to catalyse a paradigm shift, governments across the world have set goals to reduce greenhouse gas emissions of respective countries with the gradual uptake of green energy sources such as harnessing solar energy. Singapore is no exception, in recent years, the small island nation has seen the construction of numerous Floating Solar Farms (FSFs) deployed over both inland and coastal waters. As the nation progresses, FSFs will have to be constructed in increasingly rough water conditions. Therefore, it is paramount that FSF are designed thoroughly to ensure safety and longevity yet remain economically viable to ensure competitiveness against conventional fossil fuel energy sources. This report explores the design of FSF structure using a multiscale modelling approach developed by Sree et al (2022). The multiscale modelling approach is applied to optimised floater designs derived through modifications of an existing FSF structure. In applying the multiscale approach, the FSF is broken down into models with simpler representative geometries to allow for efficient analysis. The models are then analysed in both static and dynamic conditions using Finite Element Analysis to evaluate the safety of a given optimised floater design. In completing the project, this report will demonstrate how the multiscale modelling approach can be applied as a tool in the design of FSFs.